NEW MECHANISMS FOR SUPPORTING YOUTH ENTREPRENEURSHIP IN UZBEKISTAN: ANALYSIS OF 2025 PRESIDENTIAL DECREES - Xazratqulovich, Xolmaxmatov Azim; Xasanovich, Karimov Sherzod; o‘g‘li, Ismonov Navro‘zbek Obobakir (Research Focus International Scientific Journal, 2026)
This article analyzes the new opportunities for developing youth entrepreneurship and ensuring their employment provided by the Decrees of the President of the Republic of Uzbekistan dated February 14, 2025, No. 60, 61, and 62. The decrees envision mechanisms such as state targeted funds, preferential credits, venture investments, special programs for higher education graduates, and digital platforms. Expected outcomes include the employment of over 50 thousand young people, coverage of 350 thousand youths in programs, and the creation of 100 thousand additional jobs. The analysis holds scientific and practical significance, highlighting the enhancement of youth’s role in the national economy.